Coronary Artery Fistulae in Adult: Two Decades of Experience in Clinical Presentation, Angiographic Feature, and Management - Taskesen, Tuncay; Osei, Kofi; Hamilton, Russell; Ugwu, Justin; Shivapour, Daniel; Tannenbaum, Mark; Ghali, Magdi (International Journal of Angiology, 2021)
Coronary artery fistula (CAF) in adults is a rare but significant coronary artery anomaly. Main data on that rare disease were mostly obtained from case reports and small studies. In presented study, we share our two-decade experience on the clinical and angiographic characteristics of CAF.The data were collected retrospectively by analyzing the angiographic data between January 1, 2000 and December 31, 2019. Demographic data, clinical data, laboratory, and cardiac catheterization reports were reviewed.CAFs were found in 40 patients (0.06%). There were 22 male (55%) patients. The mean age was 61.2 years. Twenty-nine patients (72.5%) had small, 4 patients (10%) had medium, and 7 patients (17.5%) had large CAFs. The majority of study population had solitary CAF (n = 31, 77.5%). The pulmonary artery is the major side of fistula drainage (n = 20, 50%). The study population was divided into two groups as follow: group 1—small CAFs 29 (72.5%), group 2—medium and large CAF (MLCAF) 11 (27.5%). Patients with MLCAFs had more atrial fibrillation, abnormal coronary morphology, and multiple fistulae. In patients with hemodynamically significant CAFs, 7 (17.5%) patients had surgical ligation and 3 (7.5%) patients had transcutaneous closure. Three patients died during mean follow-up period of 5 years.The incidence and the pattern of CAFs in our study were similar to previous studies. Clinical course of small fistulae was benign. Symptomatic MLCAFs need to be treated by transcatheter or surgical way and should be individualized per patient.
Keywords: cardiac catheterization; coronary artery; fistula; coronary intervention; cardiac surgery